Application of Research Paradigms to Nutrition Practice - Boushey, Carol (Elsevier Inc., 2013)
Biological fields, including nutrition, are constantly evolving as a result of new discoveries. New findings, in turn, fuel changes to how, when, and with whom nutrition research is conducted and applied to clinical practice and populations. Nutrition researchers and practitioners can strengthen their positions in health research through being familiar with the models of research promoted and conducted across the spectrum of health fields. This chapter provides a brief overview of research models that encompass a variety of research methodologies and disciplines, such as evidence-based practice, translational research, and community-based participatory research. Examples relevant to nutrition are provided.